Higher Selective Targeting of Telomeric Multimeric G-quadruplex by Natural Product Berberine - Chen, Jixin; He, Yi; Xu, Yang; Umer, Muhammad; Anwar, Naureen; Wei, Shiya; Liu, Wenbin; Wang, Zhangqian; Gao, Chao (Current Medicinal Chemistry, 2026)
IntroductionG-quadruplexes (G4s) are non-classical high-level structures that are formed by DNA/RNA sequences and have been a promising target for developing antitumor drugs. However, it is still a challenge to find a ligand that binds to a particular G4 with selectivity. Telomeric multimeric G4s are more accessible for screening for specific ligands due to their higher-order structure compared with telomeric monomeric G4s.MethodsIn this study, the natural product berberine was found to exhibit a higher selectivity for telomeric multimeric G4 in comparison with other G4s. The mechanism of interaction between telomeric G4s and berberine was further investigated by fluorescence spectra measurements, job plot analysis, and UV titrations. We found that there are three binding sites for berberine on telomeric dimeric G-quadruplex Tel45, which are located at the 5' and 3' terminal G-quartet surfaces and the pocket between the two quadruplex units of Tel45. It was worth noting that the berberine preferred to interact within the interfacial cavity between two G4 units.ResultsMoreover, via dynamic light scattering (DLS) and native polyacrylamide gel electrophoresis (Native-PAGE) assays, it was found that the particle size of the telomeric multimeric G4s conformation was significantly increased by the addition of berberine. In contrast, the particle sizes of Tel21 did not change significantly after the addition of berberine. An immunofluorescence assay indicated that berberine induced the formation of endogenous telomeric G4 structures along with the related telomeric DNA damage response.ConclusionThis study provides a hypothetical basis for the development of natural products targeting telomeric G4 as antitumor drugs.
Keywords: electrophoresis